HASIL BELAJAR KEMAMPUAN BERPIKIR KREATIF SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE PADA MATERI POKOK KALOR KELAS X MAN 2 MODEL PEKANBARU - Guswita Pertiwi; Azhar '; Zulhelmi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study attempts to describe the students creative thinking study results and knowing the significant difference at the students creative thinking study results through the application of think talk write type of cooperative learning model in heat main subject matter class X MAN 2 Model Pekanbaru. The kind of research is pre- experimental of intac group design comparison .The population of the research is entire students class X MAN 2 Model Pekanbaru. Samples are class X MIA 4 and X MIA 5 as a class experiment and class control by the amount of students in one class 27 students. Data instrument collection is essay tests that consist 4 indicators of creative thinking indicators. Based on the results of the analysis descriptive obtained the average absorption capacity class experiment of 53.00% and class control of 53.36%. Inferential analysis shows that there are no significant differences at the creative thinking study results between class which is apply think talk write type of cooperative learning model to the conventional class in heat main subject matter class X MAN 2 Model Pekanbaru. Based on the result of the research can be concluded that students creative thinking at heat main subject matter class X MAN 2 Model Pekanbaru is not depend on the learning model application.Keywords: creative thinking , learning cooperative type think talk write